"Am I Really a Bad Parent?": Adolescent-to-Parent Abuse (AtPA) Identity and the Stigma Management Communication (SMC) Model. Issue 3 (2nd July 2016) - Brule, Nancy J.; Eckstein, Jessica J.
ABSTRACT: Applying qualitative data from grounded theory research on adolescent-to-parent abuse (AtPA), we demonstrate the utility of Meisenbach's (2010) Stigma Management Communication model. Originally developed for nonfamily contexts, this model provides an applied framework for studying stigma identity as an interactionist construct in families. Our theoretical explication and analysis of AtPA incorporates stigma, identity, and communication strategies to showcase the utility of this model for future family-focused research.